Pengaruh Kualitas Pelayanan, dan Harga Terhadap Keputusan Pembelian (Studi Kasus Roti Bakar 97) - Agus Dwi Cahya; Rizky Andrian; Renita Carla Ramadhani; Erni Dwijayanti (Universitas Hamzanwadi, 2021)
The purpose of this study is to find out the influence of service quality and price on the decision to purchase UMKM Roti Bakar 97. The variables used in this study were purchase decision variables as dependent variables, while independent variables were the influence of service quality and price. This type of research is descriptive research with quantitative approach. The subject of the study was consumers who had purchased UMKM Roti Bakar 97 products. Primary data was obtained from questionnaires from 58 respondents with purposive sampling. Then the data is analyzed using multiple linear regression analysis. The results of the study on the t test showed that the variable quality of service (X1) had no significant effect on the purchase decision (Y) with a significance value of 0.169 0.05 and a calculated t value of 1,395 t table 2,004; price variable (X2) has no effect on the purchase decision variable (Y) with a significance value of 0.173 0.05 and a calculated t value of 1,381 t table of 2,004. Based on the test results F service quality and price simultaneously influenced the purchase decision indicated by the significance value of 0.00 0.05